Forensic mental health assessment : a casebook - Heilbrun, Kirk; DeMatteo, David, 1972-; Holliday, Stephanie Brooks; LaDuke, Casey (Oxford University Press, 2014)
Forensic mental health assessment (FMHA) continues to develop and expand as a specialization. Since the publication of the First Edition of Forensic Mental Health Assessment: A Casebook over a decade ago, there have been a number of significant changes in the applicable law, ethics, science, and practice that have shaped the conceptual and empirical underpinnings of FMHA. The Second Edition of Forensic Mental Health Assessment is thoroughly updated in light of the developments and changes in the field, while still keeping the unique structure of presenting cases, detailed reports, and specific.